A Brief Study of Scoring in Chinese Writing - Sofi Zhang (Humaniora, 2013)
A writing test is a comprehensive test. It not only tests students' vocabulary, grammar, usage of language elements, but also tests their constructional ability, analytical ability, expressional ability, logical reasoning, on a variety of stylistic mastery. This paper tries to describe and summarize the problems on Chinese writing as second language learning with the theories of writing evaluation and the writing evaluation of research results.